THE REVIEW OF SOCIAL THEOLOGY AND SCIENCE ON THE BENEFITS OF VACCINE IN THE COVID-19 PREVENTIVE MEASURES - Abd Hannan; Zainuddin Syarif; Ku Abdul Muhaimin Yusof (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
The negative public perception of the vaccination is one of the most important concerns that occur while dealing with Covid-19. This viewpoint is based on the belief that vaccinations include ingredients that are prohibited by religion making their usage not halal. This study investigates the benefits of vaccinations in the Covid-19 preventive measures from a theological and scientific standpoint. This study employs qualitative research methods. Primary and secondary data were gathered from a variety of sources, including literature, information media, and statistics data. This study discovered several findings applying the maqashid al-syari'ah theory as an analytical tool: First, vaccines are medical instruments that aim to strengthen the immune system so that it can increase immunity and reduce the risk of Covid-19 transmission; Second, from the standpoint of social theology, the role of vaccines in protecting and preventing the body from transmitting Covid-19 is relevant to the dimensions of benefit found in maqashid al-syari'ah, one of which is the protection of the soul or self (hifzu al-Nafs); Third, the religious perspective plays a role in elucidating the reasons for the halal status of the Covid-19 vaccine from the standpoint of its value in social theology. In terms of science's viewpoint, it serves as a tool in articulating how the notion of self-preservation (hifzu al-Nafs) should be implemented through medical goods such as a vaccine.